A prospective comparative study between interlocking nail and locking compression plate for management of diaphyseal fractures of the humerus - Rathod, Mallesh; Kanugula, Sandeep Kumar; Raja, Pannuri (International Journal of Research in Orthopaedics, 2020)
Background: The aim of this study was to compare the outcomes between open reduction and internal fixation by locking compression plate (LCP) and closed reduction and internal fixation with anterograde interlocking nail (ILN) for the treatment of diaphyseal fractures of the humerus. Methods: This is a prospective comparative study, with diaphyseal fractures of the humerus treated by LCP in 30 patients and with ILN in 30 patients. Patients were followed up to 18 months. The clinical and radiographic outcomes were assessed in terms of union, complications, reoperation rate and functional outcome using the American shoulder and elbow surgeons’ score (ASES) and Stewart and Hundley’s criteria. Results: Union was achieved in 93.3% of patients in LCP group and 90% in ILN group. The mean blood loss in LCP group was 280±22.10 ml (160-400 ml) and in ILN group was 110±17.62 ml (70-150 ml) (p=0.001). The ASES score was 42.47±5.532 in LCP group and 40.93±6.330 in nailing group (p=0.320; p>0.05). Stewart Hundley criteria showed excellent and good results in 26/30 and 17/30 patients in LCP group and ILN group respectively (p=0.070; p>0.05). Complications and re-operation rate were higher in ILN group. Conclusions: Our study concludes that LCP can be considered a better surgical option for the management of diaphyseal fractures of the humerus as it had lower incidence of complications, less re-operation rate and better union rate. However, there is no difference between the two groups in terms of union time and functional outcome.